The use of AI in consumer experience: How independent self construal and attachment influence avoidance of similarity in beauty industry - Marques, Laura Sofia Catarino (2022)
Digital transformation has been disrupting companies’ operations, provoking significant changes in the value creation processes and on business models. The beauty industry is no exception. The potential for Artificial Intelligence is enormous as it is a sector where there is a significant amount of data being produced across various distribution channels. Furthermore, the cosmetic consumers have several needs that must be fulfilled, hence there is a strong necessity for effective personalization and targeted marketing strategies. Despite the relevance of the topic, there is a scarcity of theoretical and empirical research on customer experiences enabled by AI, which makes the present research questions: 1) does the relationship between a consumer and a beauty brand impacts consumer's willingness to experiment with new ways of shopping, powered by AI, and 2) does a shopping experience empowered by AI reinforces the uniqueness desired by consumers who perceive themselves as independents? This dissertation has an exploratory nature and includes a literature review grounded on an originally developed framework and a qualitative empirical study based on a survey. The AI tool L’Oréal Paris Skin Genius was used as reference. The result of this dissertation suggests that: 1) customers’ attachment to an established beauty brand is a key measurement to assume the level of commitment and willingness to adopt a shopping experience endorsed by AI and 2) the use of AI during the shopping experience does not influence customers’ view on the self, meaning they will still devaluate and avoid products that are perceived as commonplace.